Penilaian Kebolehgunaan Model Gamifikasi Kosa Kata Arab (M-Arab) Menggunakan Fuzzy Delphi Method (FDM) - Mohammad Najib Jaffar; Nurkhamimi Zainuddin; Mohd Adi Amzar Muhammad Nawawi; Azman Ab. Rahman; Mohammad Imran Ahmad (Universiti Sains Islam Malaysia, 2026)
International Conference of Language & Education (iLEC2025): Empowering Language and Education to Develop Madani Generation in the Era of Artificial Intelligence (AI) 17 & 18 November 2025 Organized by Universiti Sains Islam Malaysia